PENDAMPINGAN PEMANFAATAN CANVA, MENTIMETER, DAN MEDIA KARYA GURU DI SMP ISLAM AL-MAARIF 02 SINGOSARI - Setyowati, Lestari; Zubaidi, Nanang; Karmina, Sari; Anugerahwati, Mirijam; Dalopo, Firslady (Jurnal Terapan Abdimas, 2024)
Abstract. To help achieve the teaching objectives and make the learning activities runs well in the class,  teachers are encouraged to use technology-based and non-technology-based instructional media. However, not all teachers have the skills to make them. This community service aims to equip teachers in Islamic Junior High School Al-Ma'arif 02 Singosari with practical skill to create and develop instructional media, both electronic and non-electronic appropriate and relevant to their respective subjects. The methods used were conducting need analysis, coordinating, planning, implementing, reflecting, and carrying out follow-up plans for the community service. Participants in this activity were 19 teachers at Al-Maarif Islamic Junior High School 02 Singosari Malang. The workshop was held for two days on 23-24 June 2023. The results showed that the teachers were able to develop activities in non-electronic media in the form of snakes and ladders game that were adapted to their respective subjects and were able to make learning posters using Canva (95%). The results of the reflection show that all teachers (100%) got a lot of benefits from the community service and hope that similar activities were conducted more often in the future. Abstrak. Untuk menunjang kelancaran kegiatan belajar mengajar di kelas, guru seyogyanya membuat media pembelajaran berbasis teknologi maupun non teknologi. Namun tidak semua guru memiliki keterampilan untuk membuat media tersebut. Pengabdian pada masyarakat ini bertujuan untuk membekali guru di SMP Islam Al- Ma’arif 02 Singosari untuk membuat dan mengembangkan media pembelajaran baik elektronik maupun non eletronik yang sesuai dengan mata pelajarannya masing-masing. Metode yang dilakukan adalah melakukan analisis situasi, melakukan kordinasi, membuat perencanaan, melaksanakan pengabdian, melakukan refleksi, melakukan rencana tindak lanjut pengabdian. Peserta dari kegiatan ini adalah 19 orang guru di SMP Islam Al- Maarif 02 Singosari Malang. Workshop dilaksanakan selama dua hari, yaitu di tanggal 23 – 24 Juni 2023. Hasil pengabdian menunjukkan bahwa guru mampu berkreasi dengan media non elektronik berupa ular tangga yang disesuaikan dengan mata pelajarannya masing-masing, dan mampu membuat poster pembelajaran dengan menggunakan Canva (95%). Hasil refleksi menunjukkan bahwa semua guru (100%) berharap pengabdian pada masyarakat tersebut berkelanjutan, dan merasa mendapatkan banyak manfaat dari kegiatan tersebut.